El rol del psicólogo en la atención de la salud mental desde el primer nivel de atención: una revisión sistemática - Garzaniti, Ramiro (2019)
The First Care Level is one of the three levels of the health system. This level concentrate the prevention of illness, promotion of health and attention of people those are not yet ill. Objectives: The aim of this work is to create a systematic review of the published investigations about the role of the psychologist in mental health care from the first care level. Method: To achieve that I search for the investigations made about the topic of interest and collected all the World Health Organization (WHO) and the Panamerican Health Organization (PAHO) publications. To interpret the collected information I used the documentary analysis of interpretative content. I categorized the results into five axes in order to get a better comprehension. Results: The studies coincidence that the practice is centralized in individual attention framed in secondary prevention with a lack or none interdisciplinary work. Conclusions: The researchs does not coincide in the causal explanation of this work modality. The WHO and the PAHO point the major importance of the First Care Level, where through the Primary Health Care strategy it would be possible to get out of the manicomial logic, getting better results generating illness prevention and Health Promotion.